Enhancing Financial Policy Decision-Making Of Small And Medium-Sized Enterprises: The Impact Of Financial Reports Quality - Azeez, Olaoye, Ayoola; Ayodele , Adekanbi, John; Kayode, Osundeyi, Issac (Indonesian Management and Accounting Research, 2024)
Effective decision-making of Small and Medium-Sized Enterprises is paramount for their sustainability and growth. This research therefore, investigates the impact of financial reports quality on effective financial policy decision-making of Small and Medium-sized Enterprises. The research employs a quantitative approach using questionnaire method. Employing a survey research design, data was collected through administered questionnaires from a stratified sample of 171 participants representing various Small and Medium-sized Enterprises in Nigeria. Utilizing Multiple Regression models for analysis, the findings demonstrate a positive (0.020) significant (p < 0.05) impact of accurate income statement; a positive (0.253) significant (p < 0.05) impact of accurate statement of financial position and generally a positive (0.412) significant (p < 0.05) impact of other financial reports components on the effectiveness of financial policy decision-making of Nigerian Small and Medium-sized Enterprises. The study concluded that improving the accuracy of financial reports can substantially enhance financial policy decision-making efficacy of Small and Medium-Sized Enterprises. The research recommended the investment in staff training, quality assurance mechanisms, and regulatory oversight to improve financial literacy, transparency, and accountability, thus enhancing financial policy decision-making capabilities and fostering sustainable growth in Small and Medium-sized Enterprises globally.